Two cultures - one symbol - Shostak, O. G. (Proceedings of National Aviation University (archive), 2003)
This paper is dedicated to the question of similarities in the approach to the multilevel symbolism in Slav and Native American cultures. Ambivalent symbol of the snake is analyzed in the frame of mythological thinking. At the end the author comes to the conclusion that elements of mythological thinking are still present in everyday life and influence human behavior levels